The Relationship Between The Baby Led Weaning Method And The Incidence Of Choking In Infants - Holilah Holilah; Nanik Yuliwati (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: The Method Of Giving Mp-Asi That Can Be Given By Parents To Babies To Increase The Nutritional Adequacy Of Babies After Carrying Out Exclusive Breastfeeding For 6 Months Includes The Blw (Baby Led Weaning) Method. Giving Complementary Foods Through The Baby Led Weaning Method Is Also Widely Opposed Because Babies Are At Risk Of Choking. Purpose Of Writing: To Find Out The Relationship Between The Baby Led Weaning Method And Choking Incidents In Infants. Research Methods: This Type Of Quantitative Research With A Cross Sectional Study Design, The Sample In This Study Amounted To 72 People, The Chi Square Statistical Analysis Test. Results: There Is No Relationship Between The Baby Lead Weaning Method And Choking At Posyandu Kelapa Indah 7 With A P-Value Of 0.850 (Α = 0.05). Conclusions And Suggestions: The Results Of This Study Are Expected To Increase Mothers' Knowledge And Understanding Of The Baby Lead Weaning Method As A New Method Of Giving Complementary Foods And To Reduce Mothers' Concerns About Choking Due To Blw.